Effect of Glucose on Liposome–Plasma Protein Interactions: Relevance for the Physiological Response of Clinically Approved Liposomal Formulations. Issue 2 (21st October 2018) - Palchetti, Sara; Digiacomo, Luca; Pozzi, Daniela; Zenezini Chiozzi, Riccardo; Capriotti, Anna Laura; Laganà, Aldo; Coppola, Roberto; Caputo, Damiano; Sharifzadeh, Mohammad; Mahmoudi, Morteza; Caracciolo, Giulio
Abstract: Recently, the concept is emerging that the reduced success of nanoparticles in clinical practice is due to the adsorption of the "biomolecular corona (BC), " which alters their biological identity. Apart from protein variations, alterations in the human metabolome may change the BC decoration, which has poorly been addressed so far. Here, glucose is used as a model metabolite and how the interactions between liposomes (as a model nanoparticle) and plasma proteins are influenced by normal and diabetic sugar blood levels is explored. As model liposomes, Doxoves and Onivyde are used that are used for the treatment of breast and metastatic pancreatic cancer, respectively. It is shown that glucose does affect the structure and composition of BC. The biological effects of liposome–BC complexes are investigated in MCF 7 and MDA‐MB‐231 breast cancer cells for Doxoves and in pancreatic adenocarcinoma (PANC‐1) and insulinoma (INS‐1) cells for Onivyde. In the presence of glucose, the cellular toxicity of liposome–protein complexes and uptake by human monocytic THP1 cell line increases. These results demonstrate that alterations in glucose concentration, and more generally changes in the human metabolome, may play a fundamental role in the biological identity of liposomes and, consequently, on their in vivo physiological readouts including therapeutic efficacy. Abstract : Abnormal glucose concentration may affect structure and composition of the liposome‐biomolecular corona and, in turn, their anticancer efficacy. On a larger scale, this change may alter therapeutic outcomes of liposomal drugs in a patient‐specific manner (i.e., people with and without alterations in glucose concentration).